The Improvement of Solar Cell Output Power Using Cooling and Reflection from Mirror - Budiyanto Budiyanto; Fadliondi Fadliondi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper explains the experimental investigation to improve the output power of solar cell using cooling and light reflection from mirrors. The results show that by adding mirror, the current and output power of solar cell increase but the open circuit voltage and maximum power voltage decrease due to heat. By adding cooling, the open circuit voltage and the maximum power voltage are improved, so the output power also increases.